2019
DOI: 10.2196/15298
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Outrage in Response to a School-Based Substance Use Survey: Qualitative Analysis

Abstract: Background School-based alcohol, tobacco, and other drug use (ATOD) surveys are a common epidemiological means of understanding youth risk behaviors. They can be used to monitor national trends and provide data, in aggregate, to schools, communities, and states for the purposes of funding allocation, prevention programming, and other supportive infrastructure. However, such surveys sometimes are targeted by public criticism, and even legal action, often in response to a lack of perceived appropriat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The most common protocol used in longitudinal matching has been to use a combination of gender, race, and various snippets of personal information that are theoretically memorable (eg, middle initial, birth month, and mother's initial), as in the study by Kearney et al [52]. However, although such a method is generally a secure way of matching surveys without identifying individual participants, it may cause concern among parents or youth [53].…”
Section: Data Matchingmentioning
confidence: 99%
“…The most common protocol used in longitudinal matching has been to use a combination of gender, race, and various snippets of personal information that are theoretically memorable (eg, middle initial, birth month, and mother's initial), as in the study by Kearney et al [52]. However, although such a method is generally a secure way of matching surveys without identifying individual participants, it may cause concern among parents or youth [53].…”
Section: Data Matchingmentioning
confidence: 99%
“…In reviewing matching data from a large cluster, randomized trial, we identified that our approach was feasible and produced acceptable match rates in the short term. While our observed matching rate likely could have been improved by the addition of such elements, such as birth month, which had only a 1.5% mean error rate in Audette et al’s (2020) meta-analysis, each additional personalized element may increase the risk of participant or observer concern with the study (Gassman et al, 2019). School and community support for research, even when it is benign and/or potentially beneficial with few possible detrimental outcomes, may rest not only on actual adherence to ethical conduct of research but also on affirmatively creating an appearance that this is so (where it may not be obvious; Gassman et al, 2016; Gassman et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…While our observed matching rate likely could have been improved by the addition of such elements, such as birth month, which had only a 1.5% mean error rate in Audette et al’s (2020) meta-analysis, each additional personalized element may increase the risk of participant or observer concern with the study (Gassman et al, 2019). School and community support for research, even when it is benign and/or potentially beneficial with few possible detrimental outcomes, may rest not only on actual adherence to ethical conduct of research but also on affirmatively creating an appearance that this is so (where it may not be obvious; Gassman et al, 2016; Gassman et al, 2019). Additional research to identify other usable but nonpersonal longitudinal matching elements would be valuable and could potentially extend to other venues and populations such as military personnel, where confidentiality is key but prior attempts to link data have struggled (Wilson et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Car question represents a safety risk screener [50]. Internet-based survey studies are a useful tool for collecting information on drug-use patterns [50][51][52][53], they are quick and cheap to prepare, and can reach a large number of people who use drugs directly, i.e., it is a means of analysis that can provide a detailed and realistic picture of drug use and its personal and social consequences [54][55][56][57] In this study, we had both descriptive and analytical objectives. The first, descriptive, was to estimate drug abuse prevalence and its social and personal consequences based on CFRATT screening tool in the Spanish population, based on internet-based survey.…”
Section: Introductionmentioning
confidence: 99%